EDUKASI GIZI MP-ASI PADA IBU DENGAN ANAK USIA 0 -24 BULAN DI PAUD AQILA KIDS KABUPATEN KAMPAR - Zurrahmi Z.R; Sri Hardianti; Putri Eka Sudiarti (Universitas Pahlawan Tuanku Tambusai, 2021)
Mothers have an important role in providing nutrition to children because mothers are the closest people to children. However, the provision of nutrition, namely MP-ASI between one mother and another, is not the same. This is influenced by several different factors from each mother. So that the provision of MP-ASI nutrition education is still needed for mothers. Based on the situation analysis and identification of the problems mentioned above, a problem can be formulated, namely the need for complementary feeding nutrition education to mothers with children aged 0-24 months in PAUD Aqila Kids, Kampar Regency. The results of this community service are that it can increase the knowledge of mothers with children aged 0-24 months about the importance of correct and appropriate MP-ASI, how to make MP-ASI that increases baby's appetite, breastfeeding mothers are motivated to implement correct and appropriate MP-ASI making. age. This community service will continue and there will be other activities related to health and increasing maternal knowledge about complementary feeding for children aged 0-24 months in the community, especially Paud Aqilla Kids, Kampar Regency.